Monitoreo en Línea de la Corrosión en Tuberías de Flujo Bifásico en el Campo Geotérmico Miravalles - Tres,G. (2008)
The goal of this study was to evaluate the internal corrosion in a liquid-steam pipeline (type A515 low carbon steel) of the Geothermal Field of Miravalles (CGM) in Costa Rica, and to determine the corrosion thickness for future geothermal fields. The monitoring was carried out using the following techniques: linear polarization resistance (LPR), electrical resistance (ER), and weight loss. The results show for neutral or alkaline pH conditions and slightly free of oxygen, that the corrosion thickness should be 1.8 mm, in order to guarantee the integrity of the pipe over the field lifetime.